PENGARUH BUDAYA ORGANISASI DAN KOMUNIKASI ORGANISASI TERHADAP TEAMWORK KARYAWAN MELALUI KNOWLEDGE SHARING SEBAGAI VARIABEL INTERVENING PT BINTANG TEKNIK NYATA - Firmansyah, Muhammad Elny; Abadiyah, Rifdah; Andriani, Dewi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
This study aims to analyze the influence of organizational culture and organizational communication on employee teamwork with knowledge sharing as an intervening variable at PT Bintang Teknik Nyata. This study was motivated by a significant decline in the number of company projects over the past three years, which is suspected to be caused by internal problems related to organizational culture, communication, and team collaboration. This study uses a descriptive quantitative approach with data collection through questionnaires to 130 employees using probability sampling techniques. The data analysis method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.1.1.4 software. The results show that organizational culture and organizational communication have a positive and significant effect on knowledge sharing, while organizational culture has no direct effect on teamwork. Conversely, organizational communication and knowledge sharing are proven to have a positive and significant effect on teamwork. In addition, knowledge sharing fully mediates the relationship between organizational culture and teamwork and partially mediates the relationship between organizational communication and teamwork. These findings confirm that effective knowledge sharing practices are key to strengthening team collaboration, improving employee performance, and supporting the success of project-based organizations such as PT Bintang Teknik Nyata.